Intrinsic pyroelectric properties of thick, coarse grained Ba1−xSrxTiO3 ceramics. Issue 8 (June 2016) - Ianculescu, A.; Pintilie, I.; Vasilescu, C.A.; Botea, M.; Iuga, A.; Melinescu, A.; Drăgan, N.; Pintilie, L.
Abstract: The intrinsic pyroelectric properties of thick, coarse grained Ba1− x Sr x TiO3 (BST) ceramics were studied in relation with Sr content. The intrinsic values of the pyroelectric coefficient were determined directly from the frequency dependence of the measured pyroelectric signal by adapting the formalism developed for thin films deposited on thick substrates to thick and non-uniformly heated ceramics with uniform composition. Ceramic pellets, of about 1 mm thickness, with relative density of 89–95% were prepared using powder synthesized by the sol–gel method. It was found that the intrinsic pyroelectric properties are enhanced by increasing the Sr content, while other features (e.g. tetragonality, grain size, polarization, transition temperature) decrease. The best intrinsic pyroelectric properties were obtained for 30% Sr content. The present results open the possibility to use large and thick BST ceramic pellets for manufacturing detectors useful for monitoring high power lasers.